What Factors Determine the Choices between Joint Ventures and Wholly Owned Subsidiaries for MNEs to Penetrate the Japanese Market? - Su, Tzu-Hsing (2012)

(untitled)
This paper evaluates what factors determine the choices of joint venture and wholly owned subsidiary for multinational enterprises in the Japanese market in terms of resource-based theory and perspectives on subsequent entry mode, and, analyses the case of IKEA’s two entries into the Japanese market. The findings suggest that resource-based theory can explain a significant portion of a firm’s entry mode decisions in terms of the aspects of business experience, the nature of products, firm size and a firm’s ability to transfer resources. Conversely, certain variables of resource-based theory such as intangible assets and organisational culture are less significant to the choice of entry mode when it is between joint venture and wholly owned subsidiary for multinational enterprises in Japan. Moreover, perspectives on subsequent entry mode are weaker than resource-based theory in explaining the issue. Lastly, this paper provides recommendations to multinational enterprises which expect to enter, already invest, or have already once failed, in the Japanese market.